BACKYARD AQUAPONICS: CUSTOMIZED DESIGNS AND FABRICATION TECHNIQUES FOR URBAN AGRICULTURE - SONAWANE, S. A.; JADHAV, R. R.; CHAVAN, B. R.; MOHITE, A. S.; Sadawarte, R. K. (Journal of the Inland Fisheries Society of India, 2026)
This project aimed to develop and assess a backyard aquaponics system, focusing on efficient filtration. Goldfish and spinach were selected for aquaculture and hydroponics, respectively, with each 30-day experiments conducted using a fish tank, and a hydroponic unit employing two PVC pipe loops (100 x 55 cm). Two filters were tested: Filter-I with synthetic media, and Filter-II with natural media, alongside a control (no filter). Water quality parameters in Filters-I and Filters-II surpassed those of the control, with Filter-I exhibiting superior efficiency. Significant improvements in fish and plant development were observed in Filter-I and Filter-II more than the Control.